Development of Smartotc Mobile Application with Clinical Decision Support System (CDSS) to Support Pharmacists in Managing Common Cold - Ikhwan Yuda Kusuma; Khaniva Khalilia Alazhar; Peppy Octaviani; András Érszegi; Muhammad Iqbal; Muhammad Syaiful Aliim (Peneliti Teknologi Teknik Indonesia, 2026)
Common cold is a highly prevalent self-limiting respiratory illness and a frequent reason for self-medication and community pharmacy consultations. Variability in pharmacists’ clinical decision-making may affect the quality of care, highlighting the need for evidence-based decision-support tools. This study developed SmartOTC, a mobile application incorporating a Clinical Decision Support System (CDSS) to support pharmacists in managing common cold cases through symptom assessment, over-the-counter medication recommendations, patient education, and referral support. A pilot quasi-experimental before-and-after study was conducted among 10 community pharmacists in Indonesia as part of a preliminary evaluation of the application. The application was developed using Android Studio and a Python-based CDSS algorithm and evaluated through functional feasibility, task performance, usability, user experience, and expert validation assessments. SmartOTC demonstrated high technical performance, achieving a 92.73% success rate, a 0% crash rate, and a mean response time of 2.89 seconds. Significant improvements in task performance and response times were observed following implementation. However, these findings should be interpreted within the context of a pilot study with a limited sample size. The application demonstrated positive user experience and strong content validity, while usability outcomes suggested opportunities for further improvement. The findings are further limited by the single-site study setting and the absence of patient-level outcome evaluation. SmartOTC shows promise as a digital decision-support tool to support pharmacists in the management of common cold cases and warrants further evaluation in real-world pharmacy practice.